Preferential trade agreements: building blocks or stumbling blocks - case study of the US imports - Bothra, Aditi (Kansas State University, 2013)
Preferential Trade Agreements (PTAs) are known to facilitate liberalization with respect to only a few trading partners and thus they have been a topic of debate for the past two decades especially because their effect on most favored nation (MFN) tariffs is known to be ambiguous. We provide insights for analyzing whether the PTAs indeed hamper or support multilateral liberalization. Using product level official and actual tariffs we provide evidence from the United States (US) import data that the stumbling block effect on the US MFN bound tariffs is present only for goods that receive full preference in books or in actual. However, my dataset does not statistically support the stumbling block hypothesis in the case of Applied tariffs.
Keywords: Preferential trade agreements; Stumbling block; US Imports; FTA; Economics (0501)